The lunar radio flux during Leonid meteor showers and lunar eclipse - Volvach, A.E.; Berezhnoy, A.A.; Khavroshkin, O.B.; Kovalenko, A.V.; Smirnov, G.T. (Кинематика и физика небесных тел, 2005)
Significance variations of lunar radio flux at the wavelength of 2.46 cm were detected in Irbene (Latvia) during the maxima of Leonid shower on the Moon in 2000 and 2001. These results were interpreted as detection of lunar radio emission of seismic origin. However, radio observations of the Moon at the wavelength of 6 cm in Ukraine did not show any signal enhancement of lunar radio flux on November 17–19, 2001. Except meteoroid impacts, the eclipses can lead to increasing of intensity of non-thermal radio emission due to formation of micro cracks in lunar regolith when the regolith temperature during eclipses is quickly changes. The results of simultaneous observations of the full lunar eclipse at the wavelengths of 18 cm and 1.35 cm in Simeiz (Ukraine) and Pushchino (Russia) on November 8–9, 2003 are presented. According to these observations the correlation between fluctuations of lunar radio flux at both wavelengths is absent. Thus, the previously detected fluctuations of lunar flux at the wavelength of 2.6 cm may have the instrumental origin. Lunar origin of detected fluctuations could be confirmed by simultaneous observations at two radio telescopes. Our future goal is try to detect the lunar radio emission of seismic origin at the lower frequencies, because the intensity of such emission during the earthquakes increases with a decreasing frequency.